2022
DOI: 10.1002/admi.202202241
|View full text |Cite
|
Sign up to set email alerts
|

Bromide Decorated Eco‐Friendly ZnSeTe/ZnSe/ZnS Quantum Dots for Efficient Blue Light‐Emitting Diodes

Abstract: Multi‐shelled ZnSeTe/ZnSe/ZnS quantum dots (QDs) have served as a promising eco‐friendly emitter for blue quantum dot light‐emitting diodes (QLEDs). While extensive studies have concentrated on the optimization of the shell species and thickness of the multi‐shelled QDs to raise the QLED electroluminescent performance, very few reports focus on the QD surface states involving ligand and defect modulations which are essential for high‐performance QLEDs. Herein, the strategy of bromide decoration is theoreticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
1
15
1
Order By: Relevance
“…According to the previous study, the calculated binding energy value of 4MBZC fell within a reasonable range, indicating that the ligand allowed for stable passivation of the CQD surfaces, enabling the development of CQDs with an excellent PLQY. When metal halide materials are considered X-type ligands, the binding energies obtained by DFT simulations are higher than those obtained in this work. , For example, Kim et al described that the bonds between Cl – of ZnCl 2 and the zinc blende surface of the ZnSeTe/ZnS/ZnS CQDs exhibited binding energies ranging from −1.5 to −2.5 eV depending on the ligand density . This is explained by setting differences, including the ligand molecular structure, which was supposed to be a halide ion form, and a higher unsaturated coordination number of the surface atoms.…”
Section: Resultscontrasting
confidence: 54%
See 2 more Smart Citations
“…According to the previous study, the calculated binding energy value of 4MBZC fell within a reasonable range, indicating that the ligand allowed for stable passivation of the CQD surfaces, enabling the development of CQDs with an excellent PLQY. When metal halide materials are considered X-type ligands, the binding energies obtained by DFT simulations are higher than those obtained in this work. , For example, Kim et al described that the bonds between Cl – of ZnCl 2 and the zinc blende surface of the ZnSeTe/ZnS/ZnS CQDs exhibited binding energies ranging from −1.5 to −2.5 eV depending on the ligand density . This is explained by setting differences, including the ligand molecular structure, which was supposed to be a halide ion form, and a higher unsaturated coordination number of the surface atoms.…”
Section: Resultscontrasting
confidence: 54%
“…To examine the impact of the organozinc halide ligand on the optical properties and stabilities of CQDs, we selected blue-emissive ZnSeTe-based CQDs as a model system. This system is chosen among various semiconductor nanocrystal materials for the following reasons: (1) ZnSeTe is a state-of-the-art eco-friendly CQD platform that can facilitate the development of commercial-grade blue QLEDs upon further optimization of the CQDs; and (2) there are few reports on surface ligands capable of improving PLQYs in ZnSeTe-based CQD systems, , and to the best of our knowledge, there are even no reports on the utilization of organozinc halide compounds, which can provide dual-ion passivation and ensure the colloidal stability of CQDs. ZnSeTe/ZnSe/ZnSeS/ZnS CQDs were synthesized by hot injection methods with a multishelling protocol at 300 °C .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9c). 91 Meanwhile, a strong binding affinity between Br and Zn can further drive the ligand exchange to remove the superabundant oleic acid for efficient carrier transport. The density of states (DOS) calculation results of ZnS shell on the QD surface in Fig.…”
Section: Functional Modification and Optimization Of Znse(te) Qdsmentioning
confidence: 99%
“…Recently, Chen et al reported an improvement in PL QY from 39.7 to 86.2% by employing bromine for ZnSeTe QD surface passivation (Figure 3d). 49 DFT calculations demonstrated that Br ions effectively passivate QD surfaces by eliminating trap states (Figure 3e). Moreover, the stronger binding energy of Br to Zn compared with that of OA on the QD surface explains the observed ligand exchange from OA to Br (Figure 3f).…”
mentioning
confidence: 99%